Instructional technologies facilitating Open DistanceLearning: environment, interaction, and academia / Suhaida Halamy, Nurfaizah Kamarudin and Mohsinin Mohsin - Halamy, Suhaida; Kamarudin, Nurfaizah; Mohsin, Mohsinin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
The national education landscape has changed a lot because of the Coronavirus Outbreak (COVID-19) as the pandemic circumstances boost the digitization of higher education in Malaysia. Open Distance Learning (ODL) has become the new norm, with more flexibility in teaching and learning processes. Online teaching and learning should continue even after the pandemic has ended. This ensures that effective learning can be achieved in the best possible way. Adaptation to the new norms for educational institutions should be rapid for ongoing education. This issue has been an enormous movement towards online learning. Technology has been widely applied in distance education. Computer technology integration can create a successful learning environment in teaching and learning at a distance. The article discusses various technological tools that support Open Distance Learning (ODL) and analyses the features of the online platforms. Appropriate selection of technology media or tools is needed by educators or instructional designers based on their features. It may be challenging during the transition to online teaching and learning but embracing the change in this situation has positively impacted the higher education landscape.